THE MORPHOLOGICAL PROCESS OF ENGLISH CONVERSION - Dwi Astuti Wahyu Nurhayati (Pusat Pengembangan Bahasa IAIN Tulungagung, 2013)
This paper examines the morphological process of English conversion which produces the new morpheme or a process of word formation or a process of changing lexeme or changing the meaning from certain base. It includes concatenative morphology and non-concatenative (conversion included in non-catenatative). Conversion is derivational process whereby an item is adapted or converted to a new word class without the addition of an affix. The English conversion types covers direction conversion, partial conversion, deverbal, deadjectival, conversion to verb, conversion to adjective, minor categories of conversion, chnage of secondary word class: noun, verbs, adjectives, change with formal modifications.